THE REGENERATIVE POTENTIAL OF BONE TISSUE IN PATIENTS WITH GENERALIZED PERIODONTITIS STAGE II, II-III AND ANALYSIS OF IT`S ROLE DURING SURGICAL OPERATIONS ON PERIODONTAL TISSUES - G.F. Biloklytska; L.M. Panchenko; I.E. Braun (Український стоматологічний альманах)
The contemporary surgical approaches for operations on periodontal tissues have been considerably modified [5,12,15,16], became to be less invasive [5,15] and mainly aimed to provide regeneration of periodontal tissues simultaneously preventing the tissues relief [7,11,13,15,16]. However, generalized periodontitis (GP) still becomes to be the most widespread pathology of periodontal tissues which can be seen amoung working category of citizens [3-5,12,15,16]. Having big choice of modern devices and treatment protocols, the problem of effective treatment of GP appears until present times as unsolved [8,12,14,16]. GP characterized by its chonic course that can be followed by progressive periodontal tissue distraction and their loss [3,4,15,16]. During this process such significant structures as: alveolar bone, periodontal ligament and root cement, whose are characterized [3,4,7,10,12,13-16] by very slow reparation, need very longtime terms for regeneration that depends on condition of neighboring tissues of periodontal wound [3,4,12-16]. The complicity of periodontal tissues structure and their anatomical connections during functioning determine the main problems in reaching aimed regeneration using modern methods [3,4,10,11,13-16].